The Development of Kansei-Based Work Events Scale - Ibrahim, Nor Hafizah; Makhbul, Zafir Khan Mohamed; Ayob, Abu Hanifah; Mohd Lokman, Anitawati (The South East Asian Journal of Management, 2023)
Research Aims: This research aims to discover work events that influence employees’ emotional states to construct a more comprehensive Kansei-based work events scale. Design/Methodology/Approach: A mixed-method approach was adopted by combining qualitative and quantitative techniques in an Exploratory Sequential Design. Research Findings: In study 1, the Kawakita Jiro (KJ) method (i.e., focus group study) (N = 28) identified four (4) categories of work events (i.e., interpersonal, task-related, organisational policies, and infrastructure and facilities). A new category, career development, was also discovered through this qualitative inquiry. Study 2 (N = 152) and Study 3 (N = 537), which used a quantitative approach, demonstrated that negative and positive emotional experiences are strongly linked to interpersonal and task-related events. This result further indicates that the scale is reliable for measuring emotional experiences at work. Theoretical Contribution/Originality: The study captured micro and macro work events using the Kansei Engineering approach, allowing for a better understanding of emotional experiences at work. Managerial Implication in the South East Asian Context: Strategies to promote positive events and prevent negative ones through routine practices and long-term plans relevant to the South East Asian context are discussed and presented in this paper. Research Limitation & Implications: Some limitations should be considered, such as cross-sectional design, lack of investigation on other Affective Events Theory (AET) factors, and the focus on non-academic staff from public universities. Future research could expand upon this study by using a longitudinal design, a diverse sample, and additional AET factors.